Heavy Metals Uptake By Chilli Plants (Capsicum Annuum L.) Planted In Rice Husk Char And Coco Peat Media - Abdalla Al - Zrog, Abdalla Mohamed (2014)
The current study investigated the uptake of Cadmium (Cd2+) and Lead (Pb2+) by chilli plant and their effect on the plant growth and fruit quality. Kajian ini mengkaji pengambilan Kadmium (Cd2+) dan Plumbum (Pb2+) oleh pokok cili merah dan kesannya terhadap pertumbuhan tanaman dan kualiti buah-buahan.